On Reality and Law, or What was Plato Doing in Syracuse? - Šerpytytė, Rita (Problemos, 2022)
The article critically reconsiders the attitude of Giorgio Agamben, which indicate the “unreality” of the action denoted by the term “realization” as opposite to reality. This question is primarily projected into Hegel’s philosophy, in which reality is not equated with actuality (Wirklichkeit) and realization with actualization. It is considered what could be the basis of such Agamben’s approach, which does not see the need to distinguish between reality (Realität) and actuality (Wirklichkeit). The reliance on Aristotle’s metaphysics, the division of dynamis and energeia is of crucial importance in Agamben’s philosophy. It is this point that allows Agamben to apply the term “reality” to only ontologically treated realtà and at the same time contrast it with the movement of an ontic nature – realization. When raising the question – what does it mean to realize laws? – the controversial relationship between the law and reality is considered.